2011
DOI: 10.1021/jf201720z
|View full text |Cite
|
Sign up to set email alerts
|

Cultivar Evaluation and Effect of Fermentation on Antioxidant Capacity and in Vitro Inhibition of α-Amylase and α-Glucosidase by Highbush Blueberry (Vaccinium corombosum)

Abstract: The berry fruits of highbush blueberry (Vaccinium corymbosum) contain bioactive compounds with potential health benefits. The objective was to evaluate blueberries grown in southern Illinois as well as the effect of fermentation, at two different temperatures, on chemical and physical parameters. Fruits from fifteen blueberry cultivars were analyzed. Fruit diameter ranged from 12.8 mm to 18.7 mm, pH from 2.6 to 3.7, reducing sugars from 6.4% to 15.2%, total sugars from 13.9% to 21.6%, total polyphenols from 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
103
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 150 publications
(112 citation statements)
references
References 24 publications
8
103
1
Order By: Relevance
“…In some studies, the alpha-amylase inhibitory activity of berry extracts has been proposed as a possible mode of action for the glycaemic control. Thus, fifteen blueberry cultivars of Vaccinium corombosum (75) have shown in vitro alpha-amylase inhibitory activities ranging from 91.8 to 103.3 %, which correlates well with the total phenolic content of the cultivars (r= 0.85). In other study, polyphenol-rich extracts of diverse berries were tested against alpha-amylase enzyme showing that raspberries (Rubus idaeus) and rowanberries (Sorbus aucuparia) were the most effective ones (IC 50 values of 4.5 and 21.0 µg of gallic acid equivalent/ml).…”
Section: Vaccinium Corymbosum L (Ericaceae) and Other Berriesmentioning
confidence: 81%
“…In some studies, the alpha-amylase inhibitory activity of berry extracts has been proposed as a possible mode of action for the glycaemic control. Thus, fifteen blueberry cultivars of Vaccinium corombosum (75) have shown in vitro alpha-amylase inhibitory activities ranging from 91.8 to 103.3 %, which correlates well with the total phenolic content of the cultivars (r= 0.85). In other study, polyphenol-rich extracts of diverse berries were tested against alpha-amylase enzyme showing that raspberries (Rubus idaeus) and rowanberries (Sorbus aucuparia) were the most effective ones (IC 50 values of 4.5 and 21.0 µg of gallic acid equivalent/ml).…”
Section: Vaccinium Corymbosum L (Ericaceae) and Other Berriesmentioning
confidence: 81%
“…However, yellow raspberry fruit had better inhibitory activity than red raspberry fruit (Cheplick et al 2007). Blueberry proanthocyanidins had higher a-glucosidase inhibitory activity than blueberry anthocyanins (Johnson et al 2011). Ellagic acid and catechin were identified as active inhibitors of a-glucosidase along with several specific anthocyanins in ripe raspberry fruit (Zhang et al 2010).…”
Section: Discussionmentioning
confidence: 95%
“…Pharmaceutical drugs currently used in diabetes management, can cause gastrointestinal side effects due to excessive a-amylase inhibition (Bischoff et al 1985). Many phenolic metabolites from plantbased food showed a-amylase and a-glucosidase inhibitory activity in in vitro studies, and offer better strategy to manage type 2 diabetes without potential harmful side effects (McDougall et al 2005;Grussu et al 2011;Johnson et al 2011). Foods naturally rich in these phenolics have the potential to provide simple dietary strategies to regulate early stages of hyperglycemia.…”
mentioning
confidence: 99%
“…Besides the specific cultivar of Elliot and Weymouth, most blueberry wines were produced from mixed cultivars. For example, Johnson et al (2011) used 15 cultivars including Berkley, Blue Chip and Blue Haven, while in this study, the mixed cultivars were, as mentioned earlier, Star, Windsor, Emerald, Primadonna and Jewel.…”
Section: Orac Comparison Between Blueberry Wines and Grape Winesmentioning
confidence: 97%
“…Su and Chien (2007) reported that the blueberry wine making process did not really lower the anthocyanin content. There are only a few studies that have quantified the antioxidant capacity, anthocyanins and total phenols in blueberry wines, e.g., Sanchez-Moreno et al (2003), Su and Chien (2007) and Johnson et al (2011). However, no analytical quantification of the foregoing antioxidant activity and phytonutrients was found in literature for the Southern highbush blueberry wine.…”
Section: Introductionmentioning
confidence: 99%